Desire for and to Avoid Pregnancy During the Transition to Adulthood. Issue 4 (19th April 2017) - Weitzman, Abigail; Barber, Jennifer S.; Kusunoki, Yasamin; England, Paula
Abstract: Unintended pregnancies disproportionately occur among teenage women, yet little is known about the determinants of pregnancy desire among this group. The authors use a comprehensive baseline survey and data on pregnancy desires to investigate which unmarried 18‐ to 20‐year‐old women want a pregnancy, want to avoid pregnancy, and report consistent pregnancy desire and disinclination. Variables that positively predict pregnancy desire generally negatively predict desire to avoid pregnancy. Although most young women have no desire and strong disinclination in most weeks, childhood public assistance is a strong predictor of wanting pregnancy and not wanting to avoid it. Comparing nested models suggests that the effects of childhood disadvantage operate through social environments where early pregnancy is less stigmatized. Young women in serious relationships, who are depressed, and who are not pursuing postsecondary education have more desire for pregnancy and less disinclination, but little of childhood disadvantage is mediated by these factors.